2020
DOI: 10.1155/2020/7686724
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Genetic Algorithm-Based Optimization Framework for the Improvement of Near-Infrared Quantitative Calibration Models

Abstract: The global fishmeal production is used for animal feed, and protein is the main component that provides nutrition to animals. In order to monitor and control the nutrition supply to animal husbandry, near-infrared (NIR) technology was utilized for rapid detection of protein contents in fishmeal samples. The aim of the NIR quantitative calibration is to enhance the model prediction ability, where the study of chemometric algorithms is inevitably on demand. In this work, a novel optimization framework of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…GS is a traversal algorithm that tries all (c, g) parameter pairs and then finds the (c, g) parameter pair with the highest accuracy, namely the optimal parameters, through cross-validation [25]. GA is a computational model that simulates natural selection and genetic mechanisms of Darwin's theory of evolution and is a method of searching for an optimal solution [26]. PSO is a stochastic optimization method based on populations.…”
Section: Algorithmmentioning
confidence: 99%
“…GS is a traversal algorithm that tries all (c, g) parameter pairs and then finds the (c, g) parameter pair with the highest accuracy, namely the optimal parameters, through cross-validation [25]. GA is a computational model that simulates natural selection and genetic mechanisms of Darwin's theory of evolution and is a method of searching for an optimal solution [26]. PSO is a stochastic optimization method based on populations.…”
Section: Algorithmmentioning
confidence: 99%
“…In general, a three-axis accelerometer acts as the head installation of the vibration test system and is used to gather the raw vibration signal synchronously from three orthogonal axes (Xiao et al, 2017;Feng et al, 2020aFeng et al, , 2020bLi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The genetic algorithm (GA)-deep neural network non-linear regression prediction model has been proposed to achieve a robot's high-precision positioning performance under any external payload (Chen et al, 2020a(Chen et al, , 2020b. Feng et al (2020aFeng et al ( , 2020b proposed a novel optimisation framework of grid search moving window-linear predictive coding-GA for near-infrared (NIR) calibration, and experiments have shown that this algorithm provides an effective method for improving the performance of the NIR calibration models. Gao et al (2018) proposed a novel backpropagation neural network (BPNN)-PSO hybrid algorithm for the kinematic parameter identification of industrial robots with an enhanced convergence response; their results proved that the proposed algorithm has fewer iterations and a faster convergence speed.…”
Section: Introductionmentioning
confidence: 99%